Aktivitas Pembelajaran Pada Masa Pandemi COVID-19 di SMPLB dan SMALB Se-Kabupaten Pemalang Tahun Ajaran 2020/2021 - Fani Zuba Azizi; Cahyo Yuwono (Universitas Negeri Semarang, 2022)
The purpose of this study was to find out the learning model applied, facilities and infrastructure, learning process for adaptive physical education during the COVID-19 pandemic at special schools throughout Pemalang Regency for the 2020/2021 academic year. This research is a qualitative research, the methods used to collect data are interviews and questionnaires. The subjects in this study were the Principal, Adaptive Physical Education Teachers, and Students at SLB Negeri 1 Pemalang and SLB Negeri 2 Pemalang. The data analysis technique used is descriptive analysis in a narrative manner. The results showed that, 1) the learning model applied during the COVID-19 pandemic was distance or online learning using the internet and electronic devices. 2) The school provides internet quota facilities to students to support learning that is applied during the COVID-19 pandemic. 3) The physical education learning process is going well and can be followed by students from special schools throughout Pemalang Regency. From these results, it can be concluded that learning activities in SLB throughout Pemalang Regency are still carried out with online learning, and physical education learning is still carried out even though online learning